2012
DOI: 10.1073/pnas.1207514109
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem responses in the southern Caribbean Sea to global climate change

Abstract: Over the last few decades, rising greenhouse gas emissions have promoted poleward expansion of the large-scale atmospheric Hadley circulation that dominates the Tropics, thereby affecting behavior of the Intertropical Convergence Zone (ITCZ) and North Atlantic Oscillation (NAO). Expression of these changes in tropical marine ecosystems is poorly understood because of sparse observational datasets. We link contemporary ecological changes in the southern Caribbean Sea to global climate change indices. Monthly ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
76
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 39 publications
8
76
2
10
Order By: Relevance
“…The phytoplankton community shifted to smaller cells not identified in this time series, and many species that were tracked dropped in abundance 50-300-fold. This change appears to be a result of a change in grazing rates (35) and is not linked to sudden changes in temperature or the availability of nutrients. Using presence data rather than abundance means our niche models were not affected by the change in species abundances.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phytoplankton community shifted to smaller cells not identified in this time series, and many species that were tracked dropped in abundance 50-300-fold. This change appears to be a result of a change in grazing rates (35) and is not linked to sudden changes in temperature or the availability of nutrients. Using presence data rather than abundance means our niche models were not affected by the change in species abundances.…”
Section: Methodsmentioning
confidence: 99%
“…Monthly sampling at Station CARIACO recorded temperature, nitrate concentration, and the abundance of 67 dominant phytoplankton species (30,35). Irradiance in the mixed layer was estimated from monthly SeaWiFS PAR and k 490 data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal scale of these shifts was on the order of several decades, a cycle that would have gone unnoticed without a consistent and comprehensive monitoring program (Russell et al, 1971;Southward, 1995). Similarly, using 15 years of repeat measurements in the southeastern Caribbean Sea (CARIACO time--series station), Taylor et al (2012) showed how the upwelling--favorable trade winds have diminished due to the northward migration of the ITCZ, warming the ocean and decreasing primary productivity with effects cascading through the local ecosystem. In the coastal Pacific Ocean (time--series stations IMARPE, Peru and MBARI, California), the El Niño--Southern Oscillation (ENSO) has been shown to affect primary productivity in surface waters (Chavez et al, 2011), while in the oligotrophic Pacific (Hawai'i Ocean Time--series --HOT), a shift in the phytoplankton community was reported in the early 1980s that was presumably linked to changes in the North Pacific climate system (Karl et al, 2001;Corno et al, 2007).…”
Section: Global Intercomparability In a Changing Ocean: An Internatiomentioning
confidence: 99%
“…The opposite northward migration is predicted during a warmer world (2). In PNAS, Taylor et al (4) describe the response of a marine ecosystem in the marginal southern Caribbean Sea to present-day northward migrations of the ITCZ (Fig. 1).…”
mentioning
confidence: 99%